Hospital Security: Hospitals and Terrorism (Academic Journal of Internal Affairs, 2020)
Hospitals are part of the critical infrastructure and are incredibly vulnerable. Unexpected events may hinder the functioning of institutions, causing severe damage and loss of asset value and quality of service. Every hospital should be prepared for such incidents with well-developed plans and strategies. A hospital can be an ideal target for a terrorist, because a lot of civilians are taken care of (and are open) 24 hours a day, seven days a week. Unfortunately, in recent years have taken place more and more terrorist acts. (eg: 13th November 2015 Paris, and 22nd March 2016., Brussels). How are hospitals prepared for these events in Hungary and abroad? Are the Hospitals Disaster Management Plans sufficient? What kind of terrorist attacks can occur in a hospital (e.g. cyber terrorism)? In my essay I am looking for the answers to these questions and introducing the concept of hospital safety and security.
Keywords: hospital; security; soft target; terrorism